Global Health Diplomacy: A 'Deus ex Machina' for International Development and Relations - Sebastian Kevany (Kerman University of Medical Sciences, 2014)
Brugha and Bruen (2014) raise a number of compelling issues related to the interaction between politics and policy in the global health context. The first question that their views invite is whether this is, at heart, best characterized as a benign or malign influence. Many commentators have suggested that this overlap should be discouraged (see, for example, Marseille et al 2002; Thomas & Weber 2004; Fidler 2011), while others advocate a decrease in 'stove-piped' or 'siloed' approaches to government, politics, and academia (Lee et al 2010; Feldbaum 2011). To use a parallel example, the world of sport has indirectly contributed a number of notable political advances, not least the end of apartheid in South Africa as a partial result of the ban imposed on their international teams (Nixon 2002). In spite of this, organizations such as FIFA refuse to be drawn into sanctioning international football teams on non-sporting grounds (Sobolev & Gazeta 2014). The future scope and role of global health will, inevitably, face corresponding challenges.